2022
DOI: 10.1111/anae.15947
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for adult cardiac surgery: a systematic review, meta‐analysis and trial sequential analysis

Abstract: The effects of dexmedetomidine in adults undergoing cardiac surgery are inconsistent. We conducted a systematic review and meta-analysis to analyse the effects of peri-operative dexmedetomidine in adults undergoing cardiac surgery. We searched MEDLINE via Pubmed, EMBASE, Scopus and Cochrane for relevant randomised controlled trials between 1 January 1990 and 1 March 2022. We used the Joanna Briggs Institute methodology checklist to assess study quality and the GRADE approach to certainty of evidence. We assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Han, Y et al found that intraoperative application of a loading dose of dexamethasone combined with propofol during maintenance of anesthesia reduced heart rate and thus oxygen consumption by cardiac myocytes[28]. In addition, several studies have reported that perioperative use of dexmedetomidine reduced the duration of intensive care and tracheal intubation and the incidence of short-term mortality after cardiac surgery in adults [11,12,29,30]. In our study, we also found that dexmedetomidine as an anesthetic adjuvant was associated with a reduced incidence of major postoperative complications and a reduced cicu stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han, Y et al found that intraoperative application of a loading dose of dexamethasone combined with propofol during maintenance of anesthesia reduced heart rate and thus oxygen consumption by cardiac myocytes[28]. In addition, several studies have reported that perioperative use of dexmedetomidine reduced the duration of intensive care and tracheal intubation and the incidence of short-term mortality after cardiac surgery in adults [11,12,29,30]. In our study, we also found that dexmedetomidine as an anesthetic adjuvant was associated with a reduced incidence of major postoperative complications and a reduced cicu stay.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a potent, highly selective alpha-2 adrenoceptor agonist with sedative, analgesic, anxiolytic, anti-sympathetic and opioid-sparing properties [4,5].A number of studies have shown that dexmedetomidine is a useful adjunct to cardiac anesthesia [6,7] .Dexmedetomidine acts as an anesthetic adjuvant, reducing the need for opioids, inhalation anesthetics and intravenous anesthetics [8], and its anti-sympathetic activity reduces myocardial oxygen consumption by decreasing metabolism and preventing tachycardia, thereby reducing the incidence of postoperative complications in cardiac surgery, including myocardial ischemia [8,9] .Therefore, in addition to investigating the more de nitive endpoint of myocardial injury/infarction, this study examined the potential impact of dexmedetomidine on other primary endpoints, such as cardiac arrest during the postoperative period in patients undergoing cardiac surgery, congestive heart failure (CHF), and atrial brillation. Several studies have reported a reduction in cicu residence time with perioperative dexmedetomidine [10][11][12] ,suggesting that dexmedetomidine may promote rapid recovery of cardiac function in patients [12], but it is unknown whether the use of dexmedetomidine during maintenance of anesthesia for cardiac surgery has such an effect. Therefore, the speci c aim of this study was to assess whether the intraoperative use of dexmedetomidine as an anesthetic adjuvant was associated with a reduced CICU length of stay and a lower rate of major postoperative complications in patients undergoing heart valve surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Tsan et al. present the results of their systematic review, meta‐analysis and trial sequential analysis examining the link between tranexamic acid and thromboembolism in non‐cardiac surgery [10]. They included 191 randomised controlled trials with over 40,000 patients.…”
mentioning
confidence: 99%
“…We can examine in further detail the methodology used by Tsan et al. [10]. Anaesthesia has defined standards for the performing and reporting of meta‐analyses [11, 12] and identified critical steps that are recommended for consideration both to readers and to authors of meta‐analyses alike.…”
mentioning
confidence: 99%
See 1 more Smart Citation